Implementasi Penjatuhan Denda dalam Putusan Perkara Pelanggaran Pasal 17 Undang-Undang Nomor 5 Tahun 1999 Tentang Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat - Nurdiani Yusnita Sari (UNES Law Review, 2023)
This study aims to review the implementation of fines imposed by the Business Competition Supervisory Commission (KPPU) in decisions related to violations of Article 17 of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition as amended by Law Number 11 of 2020 concerning Job Creation. This study used a qualitative method by analyzing four KPPU decisions that reflect the implementation of fines for violations of Article 17 of the Antimonopoly Law. The results showed there was a mismatch between the amount of fines imposed and the losses caused by monopolistic practices and unfair business competition. This study recommends changing the KPPU's administrative sanction system from the weight of the actors to the losses incurred and felt by the public, changing the method of calculating fines based on Government Regulation Number 44 of 2021, establishing an external oversight mechanism for the KPPU, functional differentiation within the KPPU, and granting authority to reporters to file objections to the court.